THE IMPACT OF AN ANIMATED VIDEO INQUIRY TRAINING MODEL ON JUNIOR HIGH SCHOOL SCIENCE STUDENTS’ LEARNING OUTCOMES - Sitorus, Angelina Monica; Tampubolon, Johanes Joys Ronaldo; Juanta, Palma; Sitanggang, Delima (Fakultas Teknologi dan Ilmu Komputer Universitas Prima Indonesia, 2024)
The purpose of this study was to determine how the use of the questioning learning model with animated videos at Dr. Wahidin Sudirohusodo Private Junior High School in Medan, North Sumatra, impacts student learning outcomes on science materials. This study used question training, with two groups used for pretest and posttest. The study involved all students of Dr. Wahidin Sudirohusodo Private Junior High School in Medan, North Sumatra. The study involved grade VIII students spread across several parallel classes. The sample was randomly selected. There were 66 students in class VIII-1 and VIII-3. Class VIII-1 was the experimental class with 34 students, and class VIII-3 was the control class with 32 students. The results of the research show that the Inquiry Training Learning Model using animated video media on the science learning outcomes of students in the experimental class shows a good attitude compared to the control class, as seen from the increase in scores as evidenced by the experimental class’s mean score which is higher compared to the control class with the mean score for the post-test for the experimental class was 65.7647 and for the control class 42.6250.